Comparison of Antibiotic Resistance and Serotype Composition of Carriage and Invasive Pneumococci among Bangladeshi Children: Implications for Treatment Policy and Vaccine Formulation - Saha, Samir K. (American Society for Microbiology, 2003)
The nasopharyngeal carriage of Streptococcus pneumoniae is thought to pose a risk for invasive pneumococcal diseases, and the evaluation of carriage strains is thus often used to inform antibiotic treatment and vaccination strategies for these diseases. In this study, the age-specific prevalences, resistance to antibiotics, and serotype distributions of 1,340 carriage strains were analyzed and compared to 71 pneumococcal strains isolated from the cerebrospinal fluid of children under 5 years old with meningitis. Overall, the nasal carriage rate was 47%. One-fourth (26%) of the infants under 1 month of age and one-half (48%) of the infants under 12 months of age were colonized with S. pneumoniae. Rural children were colonized earlier than those from urban areas. Approximately one-fourth and one-half of the cases of pneumococcal meningitis occurred in the first 3 and 6 months of life, respectively. The respective rates of resistance for carriage and meningitis strains to penicillin (7 and 3%), cotrimoxazole (77 and 69%), and erythromycin (2 and 1%) were similar, whereas chloramphenicol resistance was lower among carriage strains (3%) than among meningitis strains (15.5%). The predominant serogroups of carriage and invasive isolates were variable and widely divergent. Thus, hypothetical 7-, 9-, and 11-valent vaccines, based on the predominant carriage strains of the present study, would cover only 23, 26, and 30%, respectively, of the serotypes causing meningitis. Further, currently available 7-, 9-, and 11-valent vaccines would protect against only 26, 43, and 48%, respectively, of these meningitis cases. In conclusion, while the surveillance of carriage strains for resistance to antibiotics appears useful in the design of empirical treatment guidelines for invasive pneumococcal disease, data on the serotypes of carriage strains have limited value in vaccine formulation strategies, particularly for meningitis cases.